Positive results of profundogluteal bypass grafting in a patient with chronic occlusion of the internal iliac artery - A. A. Moiseev; A. Ya. Bedrov; G. I. Popov; V. А. Kreil; K. А. Belova; S. M. Lazarev (Вестник хирургии имени И.И. Грекова)
The presented clinical case demonstrates the possibility of open surgical treatment of high intermittent claudication syndrome in a patient with chronic occlusion of the internal iliac artery by performing profundogluteal autogenous venous bypass grafting.